Legitimacy in Internal Conflict: Insurgency and Counterinsurgency - Joshi, Hira Lal (The Shivapuri Journal, 2024)
Max Weber's (the Weberian) concept of legitimacy is the most applied form of legitimacy but lacks the concept to address the contemporary complex issues that are prevalent in today's unconventional conflicts. Legitimacy is neither state-centric nor top-down alone. It is dynamic and may shift from one group to the other in the contested security environment and, take the bottom-up approach. The 'Western' Counterinsurgency undermines the power of the insurgents who would build their legitimacy to advance their cause. This is mainly because the 'Western' view of state formation dominates discussions on legitimacy. Insurgents and counterinsurgents both compete for legitimacy at the local level, to win over the belief and trust of the people that primarily give the legitimacy the shape of bottom-up.